2004
DOI: 10.1136/bmj.38149.566979.ae
|View full text |Cite
|
Sign up to set email alerts
|

Does the cannabinoid dronabinol reduce central pain in multiple sclerosis? Randomised double blind placebo controlled crossover trial

Abstract: Objective To evaluate the effect of the oral synthetic -9-tetrahydrocannabinol dronabinol on central neuropathic pain in patients with multiple sclerosis. Design Randomised double blind placebo controlled crossover trial. Setting Outpatient clinic, University Hospital of Aarhus, Denmark. Participants 24 patients aged between 23 and 55 years with multiple sclerosis and central pain. Intervention Orally administered dronabinol at a maximum dose of 10 mg daily or corresponding placebo for three weeks (15-21 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
289
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(303 citation statements)
references
References 45 publications
7
289
0
7
Order By: Relevance
“…Similarly, oral administration of 15 mg THC reduced the affective ratings of heat pain stimuli (Lee et al, 2013). The notion that THC influences predominantly the affective components of pain is further corroborated by THC's reported efficacy in chronic pain conditions (Abrams et al, 2007;Berman et al, 2004;Noyes et al, 1975;Nurmikko et al, 2007;Svendsen et al, 2004), especially when a psychological component such as pronounced distress is involved (Fernandez and Turk, 1992;Martin and Lichtman, 1998).…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, oral administration of 15 mg THC reduced the affective ratings of heat pain stimuli (Lee et al, 2013). The notion that THC influences predominantly the affective components of pain is further corroborated by THC's reported efficacy in chronic pain conditions (Abrams et al, 2007;Berman et al, 2004;Noyes et al, 1975;Nurmikko et al, 2007;Svendsen et al, 2004), especially when a psychological component such as pronounced distress is involved (Fernandez and Turk, 1992;Martin and Lichtman, 1998).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, Sativex®, a 1:1 THC: CBD ratio oromucosal spray formulation, is currently marketed in Canada for treatment of neuropathic pain associated with multiple sclerosis. Indeed, separate clinical studies have demonstrated that dronabinol (oral THC) (Svendsen et al, 2004), GW-2000-02 (oromucosal spray containing primarily THC), and GW-1000-02 (Sativex) (Berman et al, 2004) were marginally, yet significantly, effective against pain symptoms associated with multiple sclerosis, although each drug produced greater adverse events than placebo treatment. In that study comparisons were only made to placebo treatment.…”
Section: Preclinical and Clinical Interactions Between Thc And Cbdmentioning
confidence: 99%
“…Peak subjective ratings of dronabinol's drug effects occurred 60 min after administration, whereas dronabinol-induced decreases in pain sensitivity and increases in pain tolerance were highest about 4 h after drug administration, suggesting that the magnitude and time course of these subjective drug effects do not necessarily predict analgesia in the CPT. Clinical studies have demonstrated the analgesic effectiveness of cannabinoids including marijuana and dronabinol in neuropathic pain populations (Svendsen et al, 2004;Abrams et al, 2007;Nurmikko et al, 2007;Wilsey et al, 2008;Ellis et al, 2009;Ware et al, 2010). However, the cannabinoids proved to be less effective in attenuating other pain modalities; dronabinol (5 mg) failed to decrease postoperative pain (Buggy et al, 2003) and sensitivity to a thermal stimulus (Roberts et al, 2006), and a higher dronabinol dose (20 mg) failed to reduce acute inflammatory pain, hyperalgesia (Kraft et al, 2008), or increase pain threshold in a pressure test (Naef et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids have long been thought to be effective in reducing pain (Russo, 2008) and findings from doubleblind, placebo-controlled studies have substantiated such hypotheses demonstrating that smoked and vaporized marijuana (Abrams et al, 2007;Ellis et al, 2009;Wilsey et al, 2008Wilsey et al, , 2013, oral D 9 -tetrahydrocannabinol (THC; dronabinol), the primary psychoactive component of marijuana (Mechoulam et al, 1970;Svendsen et al, 2004), and Sativex , an oromucuosal preparation of THC and cannabidiol, decrease subjective ratings of pain in neuropathic pain populations. Because of its recent legalization for medical use in a number of US states (Hoffmann and Weber, 2010), marijuana is now being prescribed therapeutically to manage a wide variety of pain conditions (Reinarman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation